2012
DOI: 10.1557/mrc.2011.26
|View full text |Cite
|
Sign up to set email alerts
|

Dominant shear bands observed in amorphous ZrCuAl nanowires under simulated compression

Abstract: We observed the formation of dominant shear bands in model ZrCuAl metallic glass (MG) nanowires (18-nm-long) in molecular dynamics simulations, which implies size-independent incipient plasticity in MG materials. The MG nanowires were prepared using the simulated casting technique to ensure proper relaxation of sample surfaces. Under uniaxial compression, shear bands initiate at the surfaces and lead to reduced icosahedral short-range order. The shear band formation is sensitive to sample thermal-history, whic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 25 publications
(56 reference statements)
4
13
0
1
Order By: Relevance
“…Basically the NG structure resemble the one of a soft BMG. Similar, a transition in the deformation mechanism of a BMG form a localized deformation in shear bands to a homogeneous plastic flow was observed when increasing the casting cooling rate [26]. Here the softening of the glassy structure is due to the faster quenching, while in our case the NGs with very small grains get softer due to the high fraction of interfaces.…”
Section: Grain Size Effectssupporting
confidence: 79%
“…Basically the NG structure resemble the one of a soft BMG. Similar, a transition in the deformation mechanism of a BMG form a localized deformation in shear bands to a homogeneous plastic flow was observed when increasing the casting cooling rate [26]. Here the softening of the glassy structure is due to the faster quenching, while in our case the NGs with very small grains get softer due to the high fraction of interfaces.…”
Section: Grain Size Effectssupporting
confidence: 79%
“…Low quenching rate models have much higher yield stress but more obvious softening than high quenching rate C/A models. Such findings are consistent with the results in [41] which reported that amorphous nanowires with low quenching rates exhibit dominant shear bands and high yield stress while nanowires with high quenching rates undergo almost homogeneous deformation with low yield stress. However, both the two types of C/A nanolayered pillars in Fig.…”
Section: Influence Of Different Amorphous Materialssupporting
confidence: 93%
“…17,18 A recent MD study shows that ZrCuAl MG nanopillars obtained from simulated casting, 19 as opposed to traditional cutting from a glassy bulk, exhibited dominant shear banding upon simulated compression test. 20 It was reasoned that unrelaxed surfaces prepared by "cutting" lead to homogeneous flow while relaxed surfaces prepared by "casting" lead to shear banding. Furthermore, consistent with bulk MG samples, 21 MG nanopillars cooled at high quenching rate deform homogeneously while MG nanopillars cooled at low quenching rate exhibit dominant shear banding.…”
Section: Suppression Of Shear Banding In Amorphous Zrcual Nanopillarsmentioning
confidence: 99%
“…Furthermore, consistent with bulk MG samples, 21 MG nanopillars cooled at high quenching rate deform homogeneously while MG nanopillars cooled at low quenching rate exhibit dominant shear banding. 20 As MG nanopillars with high quenching rate are relatively unrelaxed structurally, it appears that the deformation mode of MG nanopillars is sensitive to the glassy state of MG nanopillars, which is in turn sensitive to the processing conditions.…”
Section: Suppression Of Shear Banding In Amorphous Zrcual Nanopillarsmentioning
confidence: 99%